Komplex a jeho vztah k motivační stránce osobnosti - Opatrný, Martin (2007)
The submitted essay focuses on the very broad and problematic idea of complex which is characterized as "king road to unconsciousness" by Car1 Gustav Jung. The aim ofthe essay is to identify and theoretically describe the fundamentals of the complex-phenomenon and to point out its relation to the motivational part of personality. The basic hypothesis of the essay is the presumption that complex might function as a positive motivational drive of human behaviour. That is the reason why it is necessary to analyze, theoretically and in detail, the process of motivation, too. Different from the specialized psychological works, this essay is to be seen from broader, cultural point of view and it summarizes both the new approaches to the field of motivation and complex and the older thoughts of the great psychologists Car1 Gustav Jung, Alfred Adler, Sigmund Freud and many others. Despite the fact that neither in the domestic nor in the foreign literature we can find any monographies that would handle the problem of complex and the related phenomenons in detail, I tried to reveal the possible relation between complex and the motivational part of personality. Based on former studies of scholar1y literature I have conc1uded that it is necessary to view both mentioned terms in various context as without it the full...